Resigners? The Experience of Black and Asian Police Officers - Barron, Anne-Marie. author. aut Link
VII, 218 p.
Keywords: Based on interviews with black, Asian and white resigners from the police, this book analyses the ways in which mundane features of employment within constabularies racialize the work of officers and leads to a decision to resign. It is argued that the occupational culture of policing remains a key context for the racialization of relationships between officers from majority and minority ethnic groups. This book adds to sociological and criminological research by grounding racialized relations within the reality of day-to-day work.